Bangladesh : Improving School Readiness with an Additional Year of Preschool - Spier, Elizabeth; Kamto Sonke, Kevin; Molotsky, Adria; Rahman, A. F. M. Azizur; Hossain, Najmul; Nahar, Zannatun; Khondker, Hosneara (World Bank, Washington, DC, 2020)
Early learning experiences promote child development and help children get prepared for school, providing children with a foundation for learning that can last into primary school and well beyond. Evidence suggests the positive impacts of these experiences are particularly pronounced for disadvantaged children, who often have limited access to learning materials and stimulation at home, and policymakers around the world have expanded access to preprimary education. But how much preprimary education do children need? Is one year enough, or do children reap additional benefits from two years of preschool?